Dictionary of chemistry and chemical engineering - Vries, L. De (ed.) Kolb, H. (ed.) (Newyork Verlag Chemie, 1978)
This dictionary defines 80,000 terms and expressions in the fields of chemistry and chemical engineering. It reflects the modern development of the vocabulary of organic, inorganic, and pharmaceutical chemistry, as well as processing technology. Useful terms in such allied scientific disciplines as physics, mathematics, electronics, instrumentation, data processing, etc. have also been included. Special attention has been given to terms used in biochemistry, molecular biology, and medicine.
Contents. -- V. 1. German/English
Keywords: Chemistry -- Dictionaries